Computer engineering and information technology - Hobbs, Fiona (Willford Press, 2016)
This book provides comprehensive insights into the field of computer engineering and information technology. Some of the diverse topics covered in this book are data processing, data analysis techniques, software engineering, multimedia, etc. Those with an interest in the field of computer engineering and information technology would find this book helpful as it contains contributions by internationally renowned scientists and experts that bring forth new frontiers for further research.